Association of Fingerprints with the ABO Blood grouping among students in Gandaki Medical College - Shrestha, R.; Hirachan, N.; Koju, S.; Shrestha, N.; Lamichhane, A. (Journal of Gandaki Medical College-Nepal, 2019)
Introduction: Dermatoglyphic study is undoubtedly the most reliable, convenient and acceptable method of individual identification since the fingerprint pattern persist same throughout the life and no two individual has similar pattern. Both blood group and dermatoglyphic pattern have genetic inheritance so an attempt has been made to analyze their correlation with gender and blood group of an individual. Methods: A cross sectional study was carried out in 200 students (105 male and 95 female), aged 17to 27 years, with prior knowledge of their blood group, of Gandaki Medical College, Pokhara, Nepal. The fingerprint patterns of both hands were recorded and patterns were observed. Results: Loop was the most common pattern registering 51.8% followed by whorls, arches and composite in both genders. Frequency of loop was higher in both male and female. Frequency of whorl was comparatively higher in male (41.3%) compared to female (38.8%). Similarly arch was more common in female (9.89%) than in male (5.05%).Frequency of loop was highest in all blood groups in both male and female; followed by whorls, arches and composite. Both loops and whorls were highest in individual with O+ blood group. Arch was found to be highest in B+ subjects. Conclusion: There was no significant association between distribution of fingerprint patterns, blood group and gender and thus prediction of gender and blood group of a person is not possible based on his fingerprint pattern.